Effect of weak magnetic fields treatment on photoluminescence of III-V single crystals - Konakova, R.V.; Red’ko, S.M.; Milenin, V.V.; Red’ko, R.A. (Semiconductor Physics Quantum Electronics & Optoelectronics, 2014)
The long-term transformations of photoluminescence of GaP, GaAs and InP single crystals treated with pulsed weak magnetic fields are obtained. The treatments were performed in two regimes, namely, single-pulse (τ = 30 ms) and multi-pulse (τ = 1.2 ms) ones, at varying magnitudes of magnetic induction. The defect structure transformations were inferred from the radiative recombination spectra in the 0.6-2.5 μm at 77 K. A possible mechanism of observed modifications related to the electron spin transformation is discussed.